The Role of Transformational Leadership and Organizational Citizenship Behavior on SMEs Employee Performance - Purwanto, Agus (AGUSPATI Research Institute, 2022)
The purpose of this study was to analyze the role of organizational citizenship behavior on the relationship of transformational leadership to the performance of SMEs. The research sample is SMEs employees with a total sample of 310 respondents in 30 SMEs. The sampling technique used is simple random sampling technique. The research instrument uses an online questionnaire and the analytical method uses Partial Least Square (PLS) with SmartPLS 3.0 software. The results show that transformational leadership has a positive and significant effect on Organizational Citizenship Behavior, transformational leadership has a positive and significant effect on employee performance and Organizational Citizenship Behavior has a positive and significant effect on employee performance, Organizational Citizenship Behavior mediates partially and positively and significantly the relationship between transformational leadership and employee performance. The implications of the results of this study indicate that transformational leadership is found to be the main factor in improving the performance of SMEs. Suggestions for research are the expansion of research orientation to a wider scope of industry and organization to obtain more comprehensive results.